2016
DOI: 10.1073/pnas.1513212113
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signaling regulates glucose homeostasis, but not adipostasis, in the zebrafish

Abstract: Leptin is the primary adipostatic factor in mammals. Produced largely by adipocytes in proportion to total adipose mass, the hormone informs the brain regarding total energy stored as triglycerides in fat cells. The hormone acts on multiple circuits in the brain to regulate food intake, autonomic outflow, and endocrine function to maintain energy balance. In addition to regulating adipose mass, mammalian leptin also plays a role in the regulation of glucose homeostasis and as a gating factor in reproductive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 48 publications
8
133
0
1
Order By: Relevance
“…Similar to reports in other fishes (Froiland et al, 2012; Michel et al, 2016), leptin does not appear to serve as an adipostat in tilapia, since neither hepatic gene expression nor circulating hormone correlate with hepatic energy stores as measured by HSI (Fig. 1) or with peritoneal fat, which changed little over 3-weeks of food deprivation in the present investigation (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to reports in other fishes (Froiland et al, 2012; Michel et al, 2016), leptin does not appear to serve as an adipostat in tilapia, since neither hepatic gene expression nor circulating hormone correlate with hepatic energy stores as measured by HSI (Fig. 1) or with peritoneal fat, which changed little over 3-weeks of food deprivation in the present investigation (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…These results demonstrate that the function of leptin at the peripheral tissues as a paracrine/autocrine factor is capable of modifying energy metabolism. In zebrafish, a leptin receptor knockout study showed that leptin played a role in the regulation of glucose homeostasis and as a gating factor in reproductive competence (Michel et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In topmouth culter Culter alburnus (Cyprinoforme), leptin mRNA expression is lower in wild populations, who have more muscle fat content than cultured fish (Wang et al, 2013), in grass carp, fish fed high fat diets have higher leptin expression (Li A. et al, 2016) than control fish, and in medaka, leptin receptor null-mutants have higher food intake and larger deposits of visceral fat than that of wild-type fish (Chisada et al, 2014), suggesting a correlation between leptin levels and fat. However, results from other studies seem to contradict this hypothesis: leptin receptor null adult zebrafish do not exhibit increased feeding or adiposity (Michel et al, 2016); In rainbow trout, leptin levels are higher in lean fish than fat fish (Salmeron et al, 2015; Johansson et al, 2016; Pfundt et al, 2016), and in Arctic charr, neither hepatic leptin expression nor plasma leptin levels correlate with fish adiposity (Froiland et al, 2012; Jørgensen et al, 2013); In murray cod Maccullochella peelii peelii (Perciforme), fish fed different experimental diets containing fish oil with or without vegetable oil have similar leptin levels (Ettore et al, 2012; Varricchio et al, 2012); In yellow catfish (Siluriforme), IP injections of human leptin reduce hepatic lipid content and the activities of lipogenic enzymes (Song et al, 2015) but Zn deficiency, which tends to increase hepatic and muscle lipid contents, does not affect leptin mRNA levels (Zheng et al, 2015). …”
Section: Hormones Involved In Food Intakementioning
(Expert classified)